Basic Properties of Concrete with Silica Fume as Supplementary Cementitious Material: Effects of Replacement Level and Particle Size - Chee Khoon, Ng; Zosher Giak, Zaine; Sim Nee, Ting (UNIMAS Publisher, 2025)
This study systematically investigates both the effects of replacement level and particle size of silica fume (SF) on concrete, identifying critical insights for optimising its use as a supplementary cementitious material (SCM). The key finding is that while SF significantly enhances mechanical properties, its optimal performance is contingent on two distinct factors: a specific replacement percentage for different strengths and a refined particle size for overall efficacy. Specifically, compressive strength was maximised at a 20%wt cement replacement, achieving 49.5 MPa at 56 days, whereas flexural strength peaked at a lower 10%wt replacement, showing a 40% increase over the control. This divergence underscores distinct strengthening mechanisms; compressive strength is governed by enhanced bulk hydration, while flexural strength is more sensitive to the densification of the interfacial transition zone (ITZ). Concurrently, any incorporation of SF markedly reduced workability, with slump values plummeting from 178 mm for the control mix to just 25 mm at 25%wt replacement, primarily due to its fine particle morphology. Beyond replacement level, particle size was identified as a decisive factor. Grinding SF from a median diameter of 76 μm to a finer median diameter of 47 μm profoundly improved concrete performance, leading to a 25% increase in early compressive strength and a remarkable more than 60% increase in flexural strength compared to mixes with larger, unground SF particles, despite a manageable reduction in slump. These results demonstrate that the sustainability and structural efficiency gains from using SF are not inherent but must be engineered. Ultimately, successfully balancing the often-competing demands of workability and strength requires a tailored approach that simultaneously optimises both its proportion in the mix and its physical fineness.